Phenylketonuria in pregnancy. (17th September 2018) - Munyame, Carol R; Vaithilingam, Nirmala; Rahman, Yusof; Vara, Roshni; Freeman, Amanda
Abstract : Key content: Phenylketonuria (PKU) is a rare, autosomal recessive metabolic disorder characterised by the body's inability to utilise the essential amino acid phenylalanine. There are three different subgroups of this disorder. Untreated or poorly controlled phenylalanine levels are associated with intrauterine growth restriction and other fetal abnormalities. Fetuses born to mothers with PKU exhibit clinical similarities to those born with fetal alcohol syndrome. Management of pregnant women with PKU is best performed under a multidisciplinary team with close monitoring of phenylalanine blood levels. Learning objectives: To understand the importance of pre‐conception counselling in women born with PKU. To understand the implications of hyperphenylalaninaemia on pregnancy and fetal outcomes. To understand the importance of involving a multidisciplinary team in the management of patients with PKU. Ethical issues: Women with poor compliance to PKU management in the prepregnancy period are at significant risk of fetal abnormalities. Should we recommend alternative reproductive options?